Conceptualization of the effect of taxation on the development of small enterprises - Kucherova, Hanna; Kravets, Olena (Technology audit and production reserves, 2017)
Small enterprises as an object of research are a lot of business entities which performance results simultaneously form the middle class in society, the flexibility and adaptability of the state’s economic system. Vulnerability and hypersensitivity to changes in environmental conditions determine the need for state support of entities, in particular, in the field of taxation. The research problem is poorly structured, which makes it expedient to use appropriate common scientific and special methods. In order to eliminate the shortcomings of existing approaches, the concept of modeling the impact of taxation on the development of small enterprises in Ukraine on the basis of identifying positive foreign experience, the results of a critical analysis of existing approaches and the formalization of a complex of economic and mathematical models is proposed. In the case of developing and implementing a fuzzy cognitive model of the taxation impact on development of small enterprises, it will be possible to take into account the unclear factors, justify the tax scenarios to increase net profit. The simulation model of the impact of the tax liability on the net profit of small businesses after construction will allow for taking into account the intergroup differences between taxpayers, as well as determine ways to reduce the level of tax burden while maintaining the volume of tax revenues. The implementation of the concept block of recursive modeling of the volumes of reinvested net profit of small enterprises will make it possible to transform the nonlinear problem into a linear one and will ensure the reliability of forecasting. In conditions of development of dynamic cluster models of small business development, it will be possible to economically justify step-by-step measures of correction of tax instruments in order to improve their efficiency level. When constructing an integral indicator of the state of small business and its changes based on the grouping of statistical indicators by categories of financial, labor and material resources, it will be possible to accurately and reliably determine the trajectory of the further development of small enterprises in Ukraine. Thus, the practical implementation of the concept will make it possible to make managerial decisions to improve tax instruments in the framework of ensuring the interests of both taxpayers and the state, in the long term, ensure the stability of their development